(3GdTgH GddGeYI aj GdSjGSI GdfGaYIs - (3YHO Gddg Hf jhSa Hf QVhGf GdfLGQj GdeGdbj, CHh GdbGSe , J (B782 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi OHQ HMceJg GdHGdZI CehQ YHGOg CeG HYO aEf ebGe GdNdGaI GdYGdjg GdJi HSW Gddg Ydi GdHSjWI CfhGQgG HJCdja eLehY ai GdSjGSI GdedhcjI hGdSjQ GdSdWGfjI jbY HgG GdEbfGY s
(3BNQgG (B:s
(3hdjYGLd GdfhGTfi GdeaSQI bHd GSJYLGdgG h GdeNGJdI bHd EecGf eLGgQJgG fLR HMeO Gddg s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI fhQ GdOjf Hc Hjge s
Keywords: (3GdSjGSI hGdGLJeGYs